Practices and digital technological resources for remote education: an investigation of Brazilian professor's profile - Lima, Mayka de Souza; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2021: Anais do XXXII Simpósio Brasileiro de Informática na Educação, 2021)
Digital Technology Resources (DTR) are considered essential in society and education for teaching-learning. Due to the Covid-19 pandemic, higher education classes have moved from face-to-face to remote teaching. Therefore, students and professors have the challenge of using DTRs as the main artifacts in their activities. This paper investigates the professors’ perceptions of DTRs in teaching practices before and during social isolation. A survey that obtained 140 responses indicates that several DTRs will remainupon the face-to-face teaching modality resumes. So, by sharing the Survey’s results, we hope to support future instructional design practices and suggest new requirements for educational software development.